Kesejahteraan Psikologi Orang Tua dari Dukungan Sosial Keluarga yang Memiliki Anak Berkebutuhan Khusus di SLB Negeri 01 Bengkulu Utara - Zuraida Zuraida; Nuspita Nuspita; Dedi Saputra (Jurnal Ilmiah Psyche, 2026)
Abstract: Parents' mental health is highly vulnerable due to the impact of having a child with special needs. After initially rejecting their child's presence, they eventually have to accept the fact that their child is different from other normal children. The mental health of parents with children with special needs is influenced by family social support. The purpose of this study was to determine the psychological well-being of parents from the social support of families who have children with special needs at SLB Negeri 01 Bengkulu Utara. A scale was used to measure the variables of psychological well-being and family social support. This study involved 32 participants. The research analysis used quantitative analysis of Karl Pearson's product moment in SPSS Version 20 Windows. The results of the study showed a substantial relationship (r.0.859 with a significance level <0.05) between psychological well-being and family social support in parents with children with special needs with a significance value below or lower than 0.05. The mental health of parents with children with special needs improves when they have strong social support from within the family. Parents' psychological well-being was in the high category (63%), and family social support was in the high category (72%).